2014
DOI: 10.1186/s12992-014-0080-x
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of diabetes in India: a review of the literature

Abstract: BackgroundDiabetes and its complications are a major cause of morbidity and mortality in India, and the prevalence of type 2 diabetes is on the rise. This calls for an assessment of the economic burden of the disease.ObjectiveTo conduct a critical review of the literature on cost of illness studies of diabetes and its complications in India.MethodsA comprehensive literature review addressing the study objective was conducted. An extraction table and a scoring system to assess the quality of the studies reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
102
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(110 citation statements)
references
References 37 publications
7
102
0
1
Order By: Relevance
“…An ongoing nationwide study in India also demonstrated a high prevalence of type 2 DM among the regions studied so far (21), which is likely to adversely impact the country's economy in future (22). There has been no systematic evaluation of glucose intolerance in Indian women with PCOS except for a few small reports (23,24), despite PCOS and DM being major public health problems (3).…”
mentioning
confidence: 93%
“…An ongoing nationwide study in India also demonstrated a high prevalence of type 2 DM among the regions studied so far (21), which is likely to adversely impact the country's economy in future (22). There has been no systematic evaluation of glucose intolerance in Indian women with PCOS except for a few small reports (23,24), despite PCOS and DM being major public health problems (3).…”
mentioning
confidence: 93%
“…3 An estimated US$ 2.2 billion would be needed to sufficiently treat all cases of type 2 diabetes mellitus (T2DM) in India. 10 India currently faces an uncertain future in relation to the potential burden that diabetes may impose on the country. It is very important to conduct studies focusing on economic evaluations to make evidence based health decisions and, consequently, to offer the best risk and cost-effective treatment choices along with better quality of life for patients with diabetes.…”
Section: Rationalementioning
confidence: 99%
“…Condliffe, Parasuraman and Pollack [11] reported that medical expenditures for diabetes patients with comorbid hypertension and obesity were significantly higher than those of patients without these comorbidities. Yesudian et al [12] summarized the literature about the economic burden of diabetes in India. In addition to the medical costs, diabetes reduces the labor supply and the productivity of patients.…”
Section: Introductionmentioning
confidence: 99%